2013
DOI: 10.1136/bmjopen-2012-001800
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiovascular and non-cardiovascular hospital admissions associated with atrial fibrillation: a Danish nationwide, retrospective cohort study

Abstract: ObjectiveTo examine the excess risk of hospitalisation in patients with incident atrial fibrillation (AF).DesignA nationwide, retrospective cohort study.SettingDenmark.ParticipantsData on all admissions in Denmark from 1997 to 2009 were collected from nationwide registries. After exclusion of subjects previously admitted for AF, data on 4 602 264 subjects and 10 779 945 hospital admissions contributed to the study.Primary and secondary outcome measuresAge-stratified and sex-stratified admission rates were calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
9
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 40 publications
4
9
1
3
Order By: Relevance
“…[25][26][27] In adjusted analyses, one may compare admission and readmission rates over time or across healthcare providers or geographic areas. In the current healthcare sector climate, methods such as those presented will provide intuitive and efficient ways to account for complex financial and socioeconomic factors that are relevant in the decisionmaking and resource utilization process.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] In adjusted analyses, one may compare admission and readmission rates over time or across healthcare providers or geographic areas. In the current healthcare sector climate, methods such as those presented will provide intuitive and efficient ways to account for complex financial and socioeconomic factors that are relevant in the decisionmaking and resource utilization process.…”
Section: Discussionmentioning
confidence: 99%
“…A Danish nationwide study reported that, within each age group, hospitalization rates for CVD and non‐CVD admissions were higher among those with AF compared with those without AF. 27 Furthermore, a 30‐year follow‐up of Olmsted County, Minnesota, residents diagnosed with lone AF, considered to be purely an electrical conduction problem, revealed that those with AF had a slightly elevated risk of developing HF or a cerebrovascular event compared with the age‐ and sex‐matched Minnesota population. 28 Moreover, in a contemporary anticoagulated AF population, 90% of deaths were related to reasons other than stroke, 29 corroborating the impact of cardiovascular comorbidities on mortality reported from the AFFIRM trial 30 and the Atrial Fibrillation and Congestive Heart Failure (AF‐CHF) trial.…”
Section: Discussionmentioning
confidence: 99%
“…По данным исследования РЕКВАЗА ФП-Тула выявлено, что больные с ФП составили 4,2% от числа госпитализированных в многопрофильный стационар. Это существенно выше, чем в популяции (1-2%), но значительно меньше, чем среди больных ССЗ, обращающихся в поликлиники (в среднем 10-20%) [1][2][3][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Discussionunclassified
“…Наибольшее число больных с ФП было выявлено в отделениях терапевтического профиля, максимальной их доля была в обоих кардиологических отделениях. Возрастной состав пациентов с ФП -люди преимущественно пожилого возраста (84,8% пациентов были старше 60 лет), что сходно с данными других госпитальных регистров [14,21,22,24].…”
Section: Discussionunclassified
See 1 more Smart Citation